Utilisation of Chat GPT in Improving Learning of Islamic Communication and Broadcasting Students at State Islamic University of Langsa - Vitra Yukadhirza; Muslem Muslem (TASAMUH, 2023)
This research aims to explain the role of Chat GPT (Generative Pre-trained Transformer) in learning for students majoring in Communication and Broadcasting Islam at the State Islamic Institute of Langsa. The phenomenological approach is used as the theoretical foundation to understand students' subjective experiences in using Chat GPT. Data was collected through in-depth interviews with three informants, namely students from the 2nd, 4th, and 6th semesters. The results of the study indicate that the use of Chat GPT provides easy access to information and assistance in understanding learning concepts. Students stated that Chat GPT helps them obtain detailed explanations, solve problems, and provide relevant additional reference sources. However, several challenges were also identified, such as less relevant answers and difficulties in formulating questions to Chat GPT. This research provides new insights into students' experiences using Chat GPT as a learning tool in higher education. These findings can serve as a reference for developing more effective learning strategies by utilizing artificial intelligence in the context of communication education.